A Review of Iqbal's Artistic and Theological Evolution in the Light of Obsolete Baang-E-dara: متروکاتِ بانگِ درا کی روشنی میں اقبال کے فکری و فنی ارتقا کا جائزہ (DARYAFT, 2022)
It has been analyzed in this essay that when Allama Iqbal published his first poetic collection “Bang-e-Dara”, it became very popular as it was keenly selected. What was its reasons? What were the aspects owing to which his inclination towards poems & Odes kept on varying of which poems did he change the titles and changed the words and lines? Due to that when ‘Bang-e-Dara’ was published, his imagination was at its peak. This has also been analyzed and tried to find out the reasons he discarded 55% of his poetic work. This has also been highlighted that the poetry of which era was largely amended by Iqbal.
Keywords: Allama Iqbal. Abandoned Bang, Dara, Mental Evolution, Cut out The best critic, Location Universality